Clinico-histopathological analysis of malignant soft tissue tumors - Deepak MB; Suchitha S; Manjunath GV; Ira Bharadwaj (Tropical Journal of Pathology and Microbiology, 2016)
Background: Aim of the study was to analyze the histopathological findings in various malignant soft tissue tumors and to study its incidence in relation to age, gender and anatomical site.Material and Method: Total of 250 cases of soft tissue lesions were analyzed retrospectively and prospectively in a period 2.5 years during June 2009 to Dec 2011. In addition to routine Haematoxylin and Eosin stained sections of all the specimens, special stains with immunohistochemical markers were done wherever necessary.Result: Of 250 lesions analyzed, 30 (12%) were soft tissue sarcomas. They were encountered slightly more in males than females. Majority of the malignant tumors occurred in fifth decade (20%). The most common site of occurrence was trunk (40%). Dermatofibrosarcoma protuberans was the most common malignant soft tissue tumor (7 cases, 23.3%). IHC studies were performed in 13 tumors for further confirmation. On gross examination 18 (60%) measured more than 5cms. Majority of soft tissue sarcomas were grade III accounting for 18 (60%) cases.Conclusion: Even though soft tissue sarcomas are rare, they are life threatening posing a significant diagnostic and therapeutic challenge and must be diagnosed early for better management. Immunohistochemistry plays a vital role in precise diagnosis and sub categorization. Grading is the most important prognostic factor and the best indicator of metastatic risk. Therefore it should be part of the pathology report for treatment stratification.